2012
DOI: 10.1038/ncb2512
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-3p controls cilia assembly by regulating CP110 and actin dynamics

Abstract: Ciliogenesis requires the removal of CP110 from the mother centriole; actin dynamics also influence ciliation, at least partly by affecting the centrosomal accumulation of ciliogenic membrane vesicles. How these distinct processes are properly regulated remains unknown. Here we show that miR-129-3p, a microRNA conserved in vertebrates, controlled cilia biogenesis in cultured cells by concomitantly downregulating CP110 and repressing branched F-actin formation. Blocking miR-129-3p inhibited serum-starvation-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(186 citation statements)
references
References 62 publications
7
179
0
Order By: Relevance
“…By using the cell type-specific expression of GFP-tagged calponin homology domain of the F-actin-binding protein utrophin (GF-P::utCH) in the sheath cells and mCherry::utCH in the socket cells, we observed GFP and mCherry fluorescence inside the sheath and socket cells, respectively (Supplementary information, Figure S2C), indicative of actin filaments in these cells. In contrast, GFP::utCH expressed in ciliated neurons did not stain cilia with GFP fluorescence but accumulated at the dendritic ending where the transition zone locates (Supplementary information, Figure S2D), which is consistent with the notion that F-actin does not assemble inside cilia but may operate around the transition zone to regulate IFT-cargo recruitment [6,9]. We further examined how the glial actin cytoskeleton is affected in animals lacking WASP function.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…By using the cell type-specific expression of GFP-tagged calponin homology domain of the F-actin-binding protein utrophin (GF-P::utCH) in the sheath cells and mCherry::utCH in the socket cells, we observed GFP and mCherry fluorescence inside the sheath and socket cells, respectively (Supplementary information, Figure S2C), indicative of actin filaments in these cells. In contrast, GFP::utCH expressed in ciliated neurons did not stain cilia with GFP fluorescence but accumulated at the dendritic ending where the transition zone locates (Supplementary information, Figure S2D), which is consistent with the notion that F-actin does not assemble inside cilia but may operate around the transition zone to regulate IFT-cargo recruitment [6,9]. We further examined how the glial actin cytoskeleton is affected in animals lacking WASP function.…”
supporting
confidence: 61%
“…Emerging evidence shows that actomyosin facilitates the recruitment of IFT materials to basal bodies in Chlamydomonas [5]. In contrast, actin-based membrane trafficking was postulated to inhibit cilium formation by removing ciliary precursors from basal bodies in mammalian cell cultures [6,7], raising the question of whether ciliogenesis in different cell types may rely on distinct actin contributions. Importantly, little is known about the role of actin in ciliogenesis in animals.…”
mentioning
confidence: 97%
“…Either silencing of actin-related protein ARP3 or treatment with actin polymerization inhibitor cytochalasin D facilitates cilia formation and promotes cilia elongation in mammalian cells [10]. Recently, we found that miR-129-3p, a microRNA conserved in vertebrates, promotes both ciliogenesis and the axoneme growth by repressing branched F-actin formation [11]. However, the regulation of ciliogenesis by actin dynamics remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been reported that actin dynamics affects ciliogenesis in mammalian cells [10,11], we tested the potential role of NudC in primary cilia assembly. Given that cilia typically form during G1 or G0 phase and disassemble around the time of mitosis, serum starvation induces ciliogenesis and addition of serum inhibits ciliation [6,19,20].…”
Section: Nudc Suppresses Primary Cilia Assemblymentioning
confidence: 99%
“…13 Consistent with these observations, nucleating factors that promote actin polymerization repress primary cilium assembly and growth whereas actin severing enzymes promote ciliogenesis. [14][15][16][17] Actin depolymerization promotes ciliogenesis by stabilizing the pericentrosomal preciliary compartment, a vesiculotubular structure that contributes to ciliogenesis, 14,15,17 and by inhibiting transcription factors from the Hippo pathway, which induce the expression of cilium disassembly factors. 17 The small GTPase RhoA plays a key role in actin network regulation.…”
Section: Introductionmentioning
confidence: 99%